2019
DOI: 10.1136/neurintsurg-2019-015093
|View full text |Cite
|
Sign up to set email alerts
|

An international multicenter retrospective study to survey the landscape of thrombectomy in the treatment of anterior circulation acute ischemic stroke: outcomes with respect to age

Abstract: BackgroundThrombectomy is an efficacious treatment for acute ischemic stroke (AIS). However, relatively few studies to date have specifically examined the impact and clinical implications of age on outcomes for thrombectomy in anterior AIS.ObjectiveTo provide a snapshot of patient metrics and outcomes with respect to age following thrombectomy for anterior AIS to supplement the current body of data for predictors of clinical outcomes in a real-world setting.MethodsData were collected for 20 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…This increase in the use of thrombectomy did not benefit patients uniformly, suggesting that the demographic, socioeconomic, and regional disparities observed in stroke care before the thrombectomy era (20-23) remain persistent today. Similar to other investigators, we also found age to be a key factor affecting mortality, especially in patients aged 80 years and older (24,25). The rate of readmission for recurrent stroke at 90 days (2.9%) was similar to that in the Multicenter Collaboration Assuming a similar recovery in the NIS cohort, an estimated 38.6% of patients in the NIS would reach a modified Rankin Scale score of 0-2 at 3 months, which is lower than the 46% who achieved this outcome in the HERMES meta-analysis, albeit equivalent to or better than the 32.6% in the Multicenter Collaboration for Endovascular Treatment of Acute Ischemic Stroke in the Netherlands trial (5) (the least selective trial, with the lowest proportion of patients reaching a modified Rankin scale score of 0-2 at 3 months).…”
Section: Rates Reasons and Risks For Readmissionsupporting
confidence: 91%
See 1 more Smart Citation
“…This increase in the use of thrombectomy did not benefit patients uniformly, suggesting that the demographic, socioeconomic, and regional disparities observed in stroke care before the thrombectomy era (20-23) remain persistent today. Similar to other investigators, we also found age to be a key factor affecting mortality, especially in patients aged 80 years and older (24,25). The rate of readmission for recurrent stroke at 90 days (2.9%) was similar to that in the Multicenter Collaboration Assuming a similar recovery in the NIS cohort, an estimated 38.6% of patients in the NIS would reach a modified Rankin Scale score of 0-2 at 3 months, which is lower than the 46% who achieved this outcome in the HERMES meta-analysis, albeit equivalent to or better than the 32.6% in the Multicenter Collaboration for Endovascular Treatment of Acute Ischemic Stroke in the Netherlands trial (5) (the least selective trial, with the lowest proportion of patients reaching a modified Rankin scale score of 0-2 at 3 months).…”
Section: Rates Reasons and Risks For Readmissionsupporting
confidence: 91%
“…However, patients who underwent thrombectomy in the NIS were older, had a higher proportion aged 80 years or older, and had more comorbidities than those who underwent thrombectomy in HERMES. Previous studies have shown higher mortality and less favorable outcomes after thrombectomy in patients aged 80 years or older (24,25) and in patients with worse premorbid disability (32). However, fewer ICA strokes in the NIS thrombectomy cohort would have favored better outcomes in this group.…”
Section: Rates Reasons and Risks For Readmissionmentioning
confidence: 99%
“…We identified a significant association between embolism and functional independence among patients with BAO that were 60 years old and younger. Perhaps, this is because younger stroke patients have a relatively better prognosis post-EVT [25], which further increases the difference in prognosis among patients with different pathological mechanisms of stroke. A retrospective study also revealed that younger patients with embolic BAO were more likely to benefit from thrombolysis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The median GCS, NIHSS, and pc-ASPECTS scores were 8 (IQR, 5-12), 23 (IQR, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 8 (IQR, 7-10), respectively. A total of thirty-four patients (20.4%) were administered intravenous alteplase prior to EVT.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…During ischemic stroke, a volume of brain tissue is immediately starved of oxygen and nutrients supplied from the blood. Thrombolytics can be used acutely to treat large vessel occlusions, but have the potential to cause hemorrhagic transformation, while for patients with large vessel occlusion of the cerebral vessels, such as the middle cerebral artery, endovascular mechanical thrombectomy can be a highly efficacious alternative 2 . The most important patient characteristic determining post-stroke outcome is the amount of penumbra that can be salvaged by restoring normal blood flow 3 5 .…”
Section: Introductionmentioning
confidence: 99%